Survey of Antibiotic Resistance and Relationship Between Eesterase (estA) Gene with Biofilm Formation in Pseudomonas Aeruginosa Strains Isolated from Burn Patients - Parisa Roshani Asl; Niloufar Rashidi; Leili Shokoohizadeh; Elahe Tajbakhsh (Fasa University of Medical Sciences, 2019)
Background & Objective: Pseudomonas aeruginosa is known as a major cause of hospital-acquired infections due to its high antibiotic resistance. Biofilm formation is an important virulence factor in P. aeruginosa infections. This pathogen produces extracellular hydrolases such as esterase estA during biofilm formation which can influence the formation and construction of biofilm. The purpose of this study was to detect the antibiotic resistance and distribution of estA gene among biofilm-producing P. aeruginosa strains isolated from burn patients. Materials & Methods: A total of 37 strains of P. aeruginosa were isolated from burn patients in Taleghani hospital in Ahvaz city and identified using standard bacteriological procedures. Antibiotic susceptibility test was performed by disk diffusion method according to the CLSI 2015. Biofilm formation was measured by micro titer plate. Existence of estA gene was detected by PCR. Results: The estA gene existed in 97.3% of isolates and 78.3% of P. aeruginosa isolates produced biofilm. Based on the results of the antibiogram test, highest rate of resistance was observed to piperacillin/ tazobactam (92%) and least resistance was to colistin (8%). Conclusion: According to the results, there was no significant correlations between presence of estA gene and biofilm formation. High level of resistance to antibiotics in P. aeruginosa is considerable.